Ultrasound in Pediatric Inflammatory Bowel Disease-A Review of the State of the Art and Future Perspectives - André Hoerning; Jörg Jüngert; Gregor Siebenlist; Ferdinand Knieling; Adrian P. Regensburger (MDPI AG, 2024)
Inflammatory bowel disease (IBD) comprises a group of relapsing, chronic diseases of the gastrointestinal tract that, in addition to adults, can affect children and adolescents. To detect relapses of inflammation, these patients require close observation, frequent follow-up, and therapeutic adjustments. While reference standard diagnostics include anamnestic factors, laboratory and stool sample assessment, performing specific imaging in children and adolescents is much more challenging than in adults. Endoscopic and classic cross-sectional imaging modalities may be invasive and often require sedation for younger patients. For this reason, intestinal ultrasound (IUS) is becoming increasingly important for the non-invasive assessment of the intestine and its inflammatory affection. In this review, we would like to shed light on the current state of the art and provide an outlook on developments in this field that could potentially spare these patients more invasive follow-up procedures.